Diastereoselective Synthesis of Six‐Membered Carbocyclic Spirooxindoles via 6π‐Electrocyclization of 3‐Dienylidene‐2‐ oxindoles. Issue 7 (29th April 2015) - Kim, Ko Hoon; Moon, Hye Ran; Lee, Junseong; Kim, Jimin; Kim, Jae Nyoung
Abstract The Wittig reaction of isatin derivatives with Morita–Baylis–Hillman bromides of cinnamaldehydes afforded 3‐dienylidene‐2‐oxindoles. These trienes were converted into the corresponding spirooxindoles in a stereoselective manner in refluxing toluene in good yields. The diastereomeric spirooxindoles could be obtained stereoselectively by adding a catalytic amount of palladium(II) acetate via the palladium‐catalyzed isomerization of EEE‐trienes to ZEE‐trienes followed by a more facile 6π‐electrocyclization process. The obtained spirooxindoles could be further functionalized by palladium‐catalyzed oxidative arylation, thionation with Lawesson's reagent, catalytic hydrogenation and Friedel–Crafts‐type reaction.